Involvement of Voltage-Gated Sodium Channel NaV1.8 in the Regulation of the Release and Synthesis of Substance P in Adult Mouse Dorsal Root Ganglion Neurons - He-Bin Tang; Eri Shiba; Yu-Sang Li; Norimitsu Morioka; Tai-Xing Zheng; Nobukuni Ogata; Yoshihiro Nakata (Elsevier, 2008)
This study was conducted to determine whether Nav1.8 contributes to the release and/or synthesis of substance P (SP) in adult mice dorsal root ganglion (DRG) neurons. The SP released from cultured DRG neurons of Nav1.8 knock-out mice exposed to either capsaicin or KCl was significantly lower than that from wild-type (C57BL/6) mice based on a radioimmunoassay. The SP level of L6 DRG in Nav1.8 knock-out mice was also lower than that in wild-type mice. After chronic constriction injury (CCI) of the sciatic nerve, the level of SP decreased in the L6 ipsilateral DRG of wild-type but not Nav1.8 knock-out mice. The preprotachykinin-A (PPT-A) mRNAs in L4 -6 DRGs of Nav1.8 knock-out mice also fell to half their normally abundant levels of expression. There were significant increases in Nav1.8 expression of the L6 contralateral DRG from wild-type mice and in the percentage of neurons expressing neurokinin-1 receptor in the cytosol of L6 DRGs from wild-type or Nav1.8 knock-out mice. These findings suggest that Nav1.8 is involved in the regulation of the release and synthesis of SP in the DRG neurons of wild-type mice. Keywords:: dorsal root ganglion (DRG), chronic constriction injury (CCI), Nav1.8 knock-out mice, preprotachykinin-A (PPT-A) mRNA, substance P (SP)